Examining the Impact of Hedonistic Lifestyles on Divorce Rates through Counseling Theories - Setiawan, Yopi; Akbarizan, Akbarizan; Ismail, Hidayatullah; Johari, Johari; AR, Muh. Ahmad Ridha (IAIN Manado, 2024)
This study explores the influence of hedonistic lifestyles on marital infidelity and relationship stability. Using a qualitative approach, data was gathered through in-depth interviews with two couples who have experienced the adverse impacts of such lifestyles on their marriages. The research findings highlight that a hedonistic orientation typically undermines both commitment and satisfaction within relationships, potentially leading to infidelity. Analysis suggests that hedonism distracts individuals from long-term relationship goals, fostering a culture of immediate gratification detrimental to marital cohesion. The study recommends integrating cognitive-behavioral therapy (CBT) techniques in couple counseling sessions to counter these effects. This intervention is aimed at helping couples develop healthier communication patterns and more effective impulse control, which are crucial for maintaining relationship stability. The implications of this research emphasize the importance of proactive therapeutic strategies that focus on enhancing interpersonal connections and managing detrimental lifestyle influences. These findings contribute to understanding how lifestyle choices affect marital dynamics and offer practical approaches for therapists working with couples facing similar challenges.